Estudo de Avaliação do Consumo de Recursos Hospitalares Associados à Administração de Trastuzumab - Sofia Andrade; Ana Santos; Aldiro Magano; Alexandra Madureira; Ana Vinagre; Carlos Góis; Fátima Falcão; Graça André; Inês Lima; Maria José Alves; Maria Nazaré Rosado; Patrícia Cavaco; et al. (Formifarma, LDA., 2014)
Objectives: To determine the cost associated with the preparation and administration of intravenous (IV) trastuzumab and to estimate the difference versus subcutaneous (SC) administration considering only the consumption of material resources (MR) and the cost associated with the time spent by the health professionals (HP) involved. Study Design: Cross-sectional study of resource consumption evaluation by interview. Location: Hospitals distributed nationally. Population: Health care professionals. Methods: Data were collected by interview to the HP involved intrastuzumab preparation and administration in the hospitals. The cost of time spent by HP was calculated by multiplying the time value of each HP by the average time of each procedure; the costs of MR were determined based on the values contained in the Health Public Supply Catalog, in Infomed or in table value provided by the manufacturer. Results: Seven Mainland Portugal hospitals were included, five public and two private, that use trastuzumab in the treatment of an average of 12 patients with HER2 + breast cancer, per week. The trastuzumab IV preparation and administration average total cost, per treatment cycle, was estimated at €35.63 (HP - €18.42; MR - €17.21) and €3.18 (PS - €3.13; RM - €0.05) for SC administration. Considering 18 treatment cycles (1 year of treatment), the cost per patient treated with trastuzumab via IV is estimated at €641.32 versus €57.20 with SC administration. Conclusions: The substitution of trastuzumab IV for the SC formulation would allow a saving of about €584 per patient per year of treatment. This study is limited by the subjectivity associated with the fact that the determination of costs was based on answers given by HP. On the other hand, the results may be undervalued due to lack of information on other costs, including costs spent by the patient.